DEVELOPMENT OF YOUTH VOLUNTEER PROGRAMS IN THE CONDITION OF THE COVID-19 PANDEMIC IN THE COMMUNITIES, NEIGHBORING TO THE AREA OF THE JOINT FORCED OPERATION IN THE EAST OF UKRAINE - Liakh, Tetiana; Lekholetova, Maryna; Kotelevets, Anastasiia; Spirina, Tetiana; Shved, Olha (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Volunteering is popular among young people in Ukraine. This is especially important for the communities, neighboring the area of the Joint Forces Operation in the East of Ukraine. However, one of the current challenges for the volunteer program development has been quarantine restrictions due to the COVID-19 pandemic. The main goal of the article is to analyze the participation of young people in volunteer programs during the quarantine restrictions related to COVID-19, in the communities neighboring the area of the Joint Forces Operation in the East of Ukraine. The authors of the study used the "rapid appraisal" technique. Thus, in May 2020, the authors interviewed 22 representatives of state and non-government organizations of Donetsk and Luhansk regions of Ukraine which implemented youth volunteer projects. The study revealed challenges caused by quarantine restrictive measures which have been grouped by authors into two groups: organizational and methodological. The answers of the respondents provided the basis to identify the positive outcomes caused by the change of the usual format of youth volunteer programs and its development: mastering of distant forms of communication by employees; development of qualitatively new ideas and introducing training programs for volunteers; increasing the ability to use the Internet to promote volunteer programs; practicing online volunteering.